Visible Foliar Injury and Physiological Responses to Ozone in Italian Provenances of Fraxinus excelsior and F. ornus - Nicla Contran; Elena Paoletti (The Scientific World Journal)
We compared leaf visible injury and physiological responses (gas exchange and chlorophyll a fluorescence) to high O3 exposure (150 nmol mol–1 h, 8 h day–1, 35–40 days) of two woody species of the same genus with different ecological features: the mesophilic green ash (Fraxinus excelsior) and the xerotolerant manna ash (F. ornus). We also studied how provenances from northern (Piedmont) and central (Tuscany) Italy, within the two species, responded to O3 exposure. Onset and extent of visible foliar injury suggested that F. excelsior was more O3 sensitive than F. ornus. The higher stomatal conductance in F. ornus than in F. excelsior suggested a larger potential O3 uptake, in disagreement to lower visible foliar injury. The higher carbon assimilation in F. ornus suggested a higher potential of O3 detoxification and/or repair. Contrasting geographical variations of ash sensitivity to O3 were recorded, as Piedmont provenances reduced gas exchange less than Tuscan provenances in F. excelsior and more in F. ornus. Visible injury was earlier and more severe in F. excelsior from Piedmont than from Tuscany, while the provenance did not affect visible injury onset and extent in F. ornus.